Debt Financing and Financial Flexibility Evidence from Proactive Leverage Increases - Denis, David J.; McKeon, Stephen B. (Review of Financial Studies, 2012)
[Firms that intentionally increase leverage through substantial debt issuances do so primarily as a response to operating needs rather than a desire to make a large equity payout. Subsequent debt reductions are neither rapid, nor the result of proactive attempts to rebalance the firm's capital structure toward a long-run target. Instead, the evolution of the firm's leverage ratio depends primarily on whether or not the firm produces a financial surplus. In fact, firms that generate subsequent deficits tend to cover these deficits predominantly with more debt even though they exhibit leverage ratios that are well above estimated target levels. Our findings are broadly consistent with a capital structure theory in which financial flexibility, in the form of unused debt capacity, plays an important role in capital structure choices.]